Dr. Emerita S. Quito was conferred the Academic Palms decoration by the french government. - Quito, Emerita S. (Animo Repository, 1985)
Dr. Emerita S. Quito, Chairperson of the Philosophy Department, was conferred the Academic Palms decoration by the French Government. It was the highest decoration conferred upon those who have major achievements in the cultural field. The award certificate was signed by the French Prime Minister Francois Mitterand. Dr. Quito was the only Filipino recipient of the award.